Readability In Translated Children’s Books: Al-gharfool As A Case Study: المقروئية في كتب الأطفال المترجمة: قصة الغرفول أنموذجا - السادة سحر , محمد; السادة سحر , محمد; مجاجي, العلجة (Maalim, 2026)
Readability is one of the most significant issues when translating for small children. Yet the concept of ‘readability of children text’ has been difficult to define when translating rhyming stories. This article studies the linguistic effect on readability through various means, such as repetition, rhyme and rhythm, and cultural differences. Based on examples taken from an English rhyming story “The Gruffalo” by Julia Donaldson, and its Arabic translation الغرفول, by Nadia Fauda and Andy Smart, the article aims at analyzing the word choice and strategies translators employ in translating repetition, including issues of equivalence and adaptation in the sense of translating proper names, food and meal times, and most importantly rhymes and rhythm, and their role in producing a highly coherent text. The main purpose of this study is to show how much translating rhyming books manipulates the process of readability, as well as the role of translators in defining the quality of any translated work.